Hubungan Paritas Dengan Kejadian Ketuban Pecah Dini DI RSUD Abdul Moeloek Periode Maret-Agustus 2017 - Aulia Ulfah Raydian; Rodiani (CV. Jasa Sukses Abadi, 2020)
Labor wiith history rupture of the membrane is at high risk for maternal and infant death, which is one of the causes of parity. Parity is one of the factors occurs premature rupture of membranes where maternal women with multiparity tend to be more susceptible to experience premature rupture of membranes. The purpose of this studyto determine the relationship between parity and PROM during inpartu.This research used observational analytic method with cross sectional design. A total sample of 249 patients were selected with consecutive sampling technique. Data collected from patient's medical record in obstetric room of RSUD Dr. H. Abdul Moeloek Lampung Province. The inclusion criteria of this research is mothers with premature rupture of membranes both vaginal delivery and cesarean section. Patients were accompanied by parity data inaccuracies, and damaged medical records were excluded from the study sample.The results showed that as many as 59 patients (23.69%) experienced with rupture of the membrane and as many as 31 (12.44%) patients who experienced rupture of the membrane with multiparity. Based on Chi-square test, p = 0.031 (p <0.05) was obtained. The conclusion of this study that there is relationship between parity with premature rupture membrane in RSUD Dr. H. Abdul Moeloek.